Covid-19 Pandemic: Challenges, Impact and Solution in Learning BTQ Subject in IT BIM Elementary School Bekasi - elkarimah, mia (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2022)
The COVID-19 pandemic has not improved until the new academic year 2021/2022. Bina Insani Muslim elementary Islamic school has designed and prepared it for offline learning namely limited face-to-face learning (PTM). However, in subsequent developments, PTM delay because alot of affected by covid. When a limited PTM instruction was opened by the Bekasi Regency Government, this Islamic school also changed the learning scheme. This study aims to find out the challenges, impacts and solutions for learning in a pandemic period that continues to experience system changes and this research is limited to Mulok BTQ learning. This study uses qualitative methods with data collection techniques in the form of interviews and observations. There are 2 aspects that become the focus of BTQ learning, namely reading and writing. Based on the observations of researchers, both offline and online learning have their respective pluses and minuses, the challenges of online learning are how the teacher's efforts to discipline students when studying at home, while offline the teacher's strategy is to maximize time, because learning time is very tight and limited makes students difficulty catching and absorbing learning material well.